TMT-Based Quantitative Proteomic Analysis Reveals the Effect of Bone Marrow Derived Mesenchymal Stem Cell on Hair Follicle Regeneration - Zhang, Chao; Li, YuanHong; Qin, Jie; Yu, ChengQian; Ma, Gang; Chen, HongDuo; Xu, XueGang (Frontiers in Pharmacology, 2021)
Hair loss (HL) is a common chronic problem of poorly defined etiology. Herein, we explored the functionality of bone marrow-derived mesenchymal stem cell (BMSC) and conditioned medium (MSC-CM) as regulators of hair follicle proliferation and regeneration, and the mechanistic basis for such activity. BMSC were cultured and identified in vitro through the induction of multilineage differentiation and the use of a CCK-8 kit. The dorsal skin of mice was then injected with BMSC and MSC-CM, and the impact of these injections on hair cycle transition and hair follicle stem cell (HFSC) proliferation was then evaluated via hematoxylin and eosin (H&E) staining and immunofluorescent (IF) staining. We then conducted a tandem mass tags (TMT)-based quantitative proteomic analysis of control mice and mice treated with BMSC or MSC-CM to identify differentially expressed proteins (DEPs) associated with these treatments. Parallel reaction monitoring (PRM) was utilized as a means of verifying our proteomic analysis results. Herein, we found that BMSC and MSC-CM injection resulted in the transition of telogen hair follicles to anagen hair follicles, and we observed the enhanced proliferation of HFSCs positive for Krt15 and Sox9. Our TMT analyses identified 1060 and 770 DEPs (fold change＞1.2 or＜0.83 and P＜0.05) when comparing the BMSC vs. control and MSC-CM vs. control groups, respectively. Subsequent PRM validation of 14 selected DEPs confirmed these findings, and led to the identification of Stmn1, Ncapd2, Krt25, and Ctps1 as hub DEPs in a protein-protein interaction network. Together, these data suggest that BMSC and MSC-CM treatment can promote the proliferation of HFSCs, thereby facilitating hair follicle regeneration. Our proteomics analyses further indicate that Krt25, Cpm, Stmn1, and Mb may play central roles in hair follicle transition in this context and may represent viable clinical targets for the treatment of HL.